SEJARAH DAN SISTEM PENDIDIKAN SEKOLAH LUAR BIASA BAGIAN A NEGERI DENPASAR BALI - I Nyoman Bayu Pramartha (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The research aims to determine: (1) Background The establishment of the School of Extraordinary Part A Denpasar. This study is fully refers to the method that has been prepared. The approach used in this study is qualitative descriptive. Determination of the informant by purposive sampling technique and developed with a snow ball technique. The collection of data through observation, interview and record-keeping. The results showed that the background of the establishment of SLB/A Negeri Denpasar caused by children with disabilities, especially blind children. Especially blind children are not getting an education. The education system in force in SLB/A Negeri Denpasar, Bali include: curriculum, educational goals, learning evaluation, education, students, educational tools and nurtured. All of these elements work together as a unit in order to realize the vision and mission of SLB/A Negeri Denpasar realize that professional and quality education for children with special needs.